The Bourne identity - Ludlum, Robert. 4 0 16; 5 (Toronto : Bantam Books, 1980)
A man has been shot and now has no memory and as he searches for his origins he comes to fear he may have been an international assassin.
Wilson's Senior High School;Wilson's Fiction;Library Journal
Keywords: 2 -- 0; 6; 20; 20; 2